THE POTENTIAL OF BAY LEAVE (SYZYGIUM POLYANTHUM) AS AN ANTI-DIABETIC AGENT - Wildan Dwi Putra Widodo; Nita Parisa; Nia Savitri Tamzil; Evi Lusiana; Nafrah Ardita; Amira Azra Arisa Putri; Sindy Bintang Permata; Aisyah Fristania Ditamor (International Journal of Islamic and Complementary Medicine, 2023)
Non-communicable disease prevalence continues to increase in Indonesia. One of the top 10 causes of death is non-communicable disease, and diabetes mellitus is on the list. Genetics, advanced age, obesity, stress, hypertension, smoking, and physical inactivity are risk factors that might result in diabetes mellitus. Despite advancements in mainstream anti-diabetic treatment, traditional medical practices continue to exist in several nations. Syzygium polyanthum is the herb that diabetic patients most frequently utilize in the traditional therapy of their illness, according to research on diabetic patients at the Health Community Center in Sering, Medan, Indonesia. The research team was interested in figuring out whether bay leaves showed any potential as an anti-diabetic agent based on the previous description. In this study, secondary literature from research publications is used in a literature review with a descriptive method. Several studies have suggested that bay leaves could potentially be used for the prevention and treatment of diabetes mellitus.